Can neurological soft signs and neurocognitive deficits serve as a combined endophenotype for Han Chinese with bipolar disorder? - Yingying Feng; Jia Song; Guorong Lin; Hong Qian; Li Feng; Zongqin Wang; Juan Wen; Chengchen Wang; Jiayuan Wang; Peifu Li; Zuohui Gao; Xiaoli Wang; et al. (International Journal of Methods in Psychiatric Research, 2023)
Abstract Background Bipolar disorder's (BD) potential endophenotypes include neurological soft signs (NSS) and neurocognitive disorders (ND). Few research, meanwhile, has coupled NSS and ND as combined endophenotypes of BD. Object This study intends to investigate NSS and ND and compare their differences in euthymic patients with bipolar disorder (EBP), their unaffected first‐degree relatives (FDR), and healthy controls (HC). Additionally, search for potential endophenotypic subprojects of NSS and ND and construct and verify a composite endophenotypic. Methods The subjects were all Han Chinese and consisted of 86 EBP, 81 FDR, and 81HC. Cambridge Neurological Inventory and MATRICSTM Consensus Cognitive Battery tested NSS and ND independently. Results All three groups displayed a trapezoidal distribution of NSS levels and cognitive abnormalities, with EBP having the most severe NSS levels and cognitive deficits, followed by FDR and HC. Among them, motor coordination in NSS and Information processing speed (IPS), Verbal learning (VL), and Working memory (WM) in neurocognitive function are consistent with the traits of the endophenotype of BD. The accuracy in differentiating EBP and HC or FDRs and HC was higher when these items were combined as predictor factors than in differentiating EBP and FDR. Conclusion These results provide more evidence that motor coordination, IPS, VL, and WM may be internal characteristics of bipolar disease. When these characteristics are combined into a complex endophenotype, it may be possible to distinguish BD patients and high‐risk groups from normal populations.